UTILIZATION OF CHIMERIC ANTIGEN RECEPTOR-T (CAR-T) CELL THERAPY AS AN INNOVATIVE THERAPY FOR NON-SMALL LUNG CANCER (NSLC) - Rusdiawan, Fairuz Octora Aulia; Kasasiah, Ahsanal (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Non-Small Lung Cancer is one of the types of lung cancer with the highest prevalence in Indonesia. So that treatment is needed in an effort to reduce the prevalence rate. Chimeric Antigen Receptor-T (CAR-T) cell therapy is known to have the potential to be an alternative treatment for these types of cancer cells. This research is made with the hope that in the future this research can be further developed by researchers, especially in Indonesia. This literature study was made using the Systematic Literature Review (SLR) design to determine the effectiveness of CAR-T cell therapy targeted at several different genes and tested on mouse xenograft models. The journals used were obtained with a publication range of 2014-2024 and 7 journals were selected based on the results of inclusion and exclusion. Based on the results of the article review, it is known that CAR-T cell therapy targeting genes has good antitumor activity efficacy obtained from the test results by measuring the volume and weight of tumors in mouse xenograft models using a caliper and Bioluminescence Imaging (BLI) irradiation method.